The impact of the use of financial technology on bank capitalization - an analytical study to foresee the application at the level of the Algerian banking environment - chegrouche, roumaissa; boufafa, widad (Journal of Research in Finance and Accounting, 2024)
This research paper aims to highlight the possibility of an impact of the relationship between bank capitalization and financial technology and try to bring it down on the Algerian banking system by relying on the descriptive analytical approach and comparative method of a set of published studies and reports. The study found that there is a relationship between bank capitalization and financial technology, represented by a direct relationship, i.e. whenever there is the use of innovative financial technology and its technologies allow the bank to carry out the capitalization process, this indicates the possibility of relying on this relationship to activate the course of Algerian reforms scheduled for 2024, according to the latest statement of the president of the Republic, who considered 2024 the year of Algerian reform